2015
DOI: 10.1016/j.bandc.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Fixation to features and neural processing of facial expressions in a gender discrimination task

Abstract: Early face encoding, as reflected by the N170 ERP component, is sensitive to fixation to the eyes. Whether this sensitivity varies with facial expressions of emotion and can also be seen on other ERP components such as P1 and EPN, was investigated. Using eye-tracking to manipulate fixation on facial features, we found the N170 to be the only eye-sensitive component and this was true for fearful, happy and neutral faces. A different effect of fixation to features was seen for the earlier P1 that likely reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
52
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(77 citation statements)
references
References 83 publications
20
52
5
Order By: Relevance
“…A face stimulus was then presented offset so as to put the desired feature in fovea, at the location of the fixation cross. We expected to replicate the findings of Neath and Itier (2015) regarding low-level stimulus position effects on the P1, as well as the larger N170 amplitude for fixation to the eyes compared to the nose and mouth (see also de Lissa et al, 2014;Nemrodov, Anderson, Preston, & Itier, 2014). We also hoped to reproduce their distinct spatio-temporal pattern of fear and happiness effects.…”
Section: Role Of Facial Features In the Processing Of Facial Expressionmentioning
confidence: 75%
See 4 more Smart Citations
“…A face stimulus was then presented offset so as to put the desired feature in fovea, at the location of the fixation cross. We expected to replicate the findings of Neath and Itier (2015) regarding low-level stimulus position effects on the P1, as well as the larger N170 amplitude for fixation to the eyes compared to the nose and mouth (see also de Lissa et al, 2014;Nemrodov, Anderson, Preston, & Itier, 2014). We also hoped to reproduce their distinct spatio-temporal pattern of fear and happiness effects.…”
Section: Role Of Facial Features In the Processing Of Facial Expressionmentioning
confidence: 75%
“…Some studies have suggested that the EPN reflects the neural activity related to the processing of the emotion that is superimposed onto the normal processing of the face. This superimposed activity would sometimes start around the N170 and be responsible for the emotional effects reported for the N170 (Leppänen et al, 2008;Rellecke et al, 2011;Schupp et al, 2004), although it seems largest after the N170 peak and around the visual P2 (see Neath & Itier, 2015, for a recent example). In other words, the emotion effect on the N170 would actually reflect superimposed EPN activity (Rellecke et al, 2011;Rellecke, Sommer, & Schacht, 2012;Schacht & Sommer, 2009).…”
Section: Early Event-related Potentials In Facial Expression Researchmentioning
confidence: 99%
See 3 more Smart Citations